Redox-active benzoquinone-intercalated layered vanadate for high performance zinc-ion battery: Phenol-keto conversion and the anchoring effect of V-O-V host framework - Liu, Chang Lin; Cao, Tong; Wang, Zhao Peng; Li, Kai; Gong, Yun; Zhang, Da Liang (Electrochimica acta, 2022)
•(o-BQ)0.25V2O5·0·5H2O and (p-BQ)0.25V2O5·0·5H2O (BQ = benzoquinone) were synthesized.•Rietveld refinements and HAADF-STEM reveal the successful intercalation of BQ into V2O5.•(p-BQ)0.25V2O5·0·5H2O shows an excellent rate performance and an ultralong cycle life.•The sandwiched BQ in layered V2O5 can be prevented from leaching into the electrolyte.•DFT calculations disclose a small Zn2+-migration barrier in (p-BQ)0.25V2O5·xH2O. Utilizing a facile one-step hydrothermal technique, oxygen-deficient (o-BQ)-VO and (p-BQ)-VO nanosheets were synthesized, which were formulated as (o-BQ)0.25V2O5·0·5H2O and (p-BQ)0.25V2O5·0·5H2O (BQ = benzoquinone), respectively. Rietveld refinements and high-angle annular dark-field (HAADF)-scanning transmission election microscope (STEM) reveal the successful intercalation of o-BQ or p-BQ into the layered V2O5 with large interlayer spacings of ∼ 13.7 Å, in which all the V centers are coordinatively unsaturated due to the elongation of V-O bonds. (p-BQ)-VO shows an excellent rate performance of 487/446/405/371/333/280 mAh g−1 at 0.1 ∼ 5 A g−1 and an ultralong cycle life with a capacity retention of 96.0% after 4000 discharge/charge cycles at 5 A g−1, which is due to the dual redox-activity from BQ and vanadium oxide. The phenol-keto conversion of BQ can provide extra capacity. Furthermore, the sandwiched BQ in layered V2O5 can be prevented from leaching into the electrolyte. On the other hand, (p-BQ)-VO shows better electrochemical performance than (o-BQ)-VO, indicating that the redox property of quinone is associated with the para- or ortho-position of keto-group and their possible coordination modes with Zn2+. Density functional theory (DFT) calculations disclose that the deep intercalation of Zn2+ on certain site in (p-BQ)-VO can improve electron conductivity, giving rise to enhanced electrochemical behavior. And the Zn2+-migration along b axis of the (p-BQ)-VO cell shows a small energy barrier of 0.80 eV, thus leading to the outstanding rate and cycling performances. Redox-active benzoquinone (BQ)-intercalated layered vanadate (p-BQ)0.25V2O5·0·5H2O exhibits excellent rate performance and ultralong cycle life in zinc-ion battery, which is due to the dual redox-activity from BQ and vanadium oxide. Furthermore, the sandwiched BQ in layered V2O5 can be prevented from leaching into the electrolyte. DFT calculations disclose a small Zn2+-migration barrier of 0.80 eV. [Display omitted]